Comparative evaluation of xerostomia among diabetic and nondiabetic subjects wearing complete denture - Manikandan Sundaram; Saranya Manikandan; Balakrishnan Satheesh; Deenadayalan Srinivasan; Dinakaran Jayapal; Dhivya Kumar (Wolters Kluwer Medknow Publications, 2020)
Background: Diabetes mellitus represents a group of metabolic diseases that are characterised by hyperglycaemia due to a total or relative lack of insulin secretion and insulin resistance or both. Diabetes mellitus patients present with a higher susceptibility to infections due to a deficiency in polymorphonuclear leukocytes, as a result of vascular alterations and neuropathies. An increased risk of infections has been observed in complete denture wearing subjects with xerostomia. The objective of this study was to compare diabetic and non-diabetic subjects wearing complete dentures regarding xerostomia of different age group. Materials and Methods: A cross-sectional study was conducted among 50 subjects, 25 with and 25 without a diagnosis of diabetes, were matched for gender, race, and age. Results: In this study we intended to compare diabetic and non-diabetic subjects wearing complete dentures regarding xerostomia and we found that xerostomia was more associated with diabetic denture wearer group in comparison with the non-diabetic denture wearers with a significant P value of <0.05. Conclusion: These results indicate that xerostomia should be diagnosed and effectively managed before any complete denture therapy is initiated in diabetic denture wearing patients to improve the quality of life.